Illustrations for Dante's "Inferno" - Owen, Rachel 1968-2016; Bowe, David 1986- (Bodleian Library Publishing, 2021)
Rachel Owen's hauntingly beautiful illustrations for Dante's Inferno take a radically new approach to representing the world of Dante's famous poem. The images combine the artist's deep cultural and historical understanding of 'The Divine Comedy' and its artistic legacy with her unique talent for collage and printmaking. These illustrations, casting the viewer as a first-person pilgrim through the underworld, prompt us to rethink Dante's poem through their novel perspective and visual language. 0Owen's work, held in the Bodleian Library and published here for the first time, illustrates the complete cycle of thirty-four cantos of the Inferno with one image per canto. The illustrations are accompanied by essays contextualising Owen's work and supplemented by six illustrations intended for the unfinished Purgatorio series. Fiona Whitehouse provides details of the techniques employed by the artist, Peter Hainsworth situates Owen's work in the field of modern Dante illustration and David Bowe offers a commentary on the illustrations as gateways to Dante's poem. Jamie McKendrick and Bernard O'Donoghue's translations of episodes from the 'Inferno' provide complementary artistic interpretations of Dante's poem, while reflections from colleagues and friends commemorate Owen's life and work as an artist, scholar and teacher. This stunning collection is an important contribution to both Dante scholarship and illustration
Keywords: Dante -- Alighieri -- 1265-1321 -- Inferno; Owen, Rachel -- 1968-2016; Illustration; Owens, Rachel / 1968-2016; Dante Alighieri / 1265-1321 / Inferno / Illustrations; Inferno (Dante Alighieri); Illustrated works